Milk production and fat composition on the monthly milking day control of river cow buffaloes (Bubalus bubalis) at the Granma province in Cuba - Méndez, M.; Fraga, L. M.; Amorim, A. [UNESP]; Mora, M. (My University, 2010)
It was evaluated milk production and fat percent composition of monthly control milking day on bubaline herds at the Granma province in Cuba using 2140 records for monthly milking day and 1620 for fat percent composition of 500 lactations corresponding to 150 cow buffaloes of Buffalypso breed. Calvings occured between years 1997 to 2005. It was employed the SAS (2007), versión 9.1.13 employing Mixed Model equations with the effects of contemporary groups, control date and the interaction of herd x control date as fixed and herd and ear tag within herd as random effects. Repeatabilities were calculated for both traits and modelation of the lactation curve. It was considered that milk production on the control day of the cow buffaloes was low and that fat percent was situated within the values reportated in this species. The repeatabilities were generally within the rank of medium to high. The modelation of lactation and fat percent curves adjusted by lineal models had high adjusted determination coefficients when it was used the quadratic logarithmic model. It is recomended that selection of cow buffaloes for milk production can be conducted using repeated records of monthly day milking controls which had the higher repeatabilities values and that the curves were well adjusted with the Mixed Model employed.
Keywords: Day control milk fat lactation curve